(untitled) (AYUSHDHARA, 2025)
ynthetic drugs often have adverse side effects, whereas Ayurvedic formulations are known for their efficacy and safety. Darvyadi Ghrita, a traditional Ayurvedic formulation, is indicated for the treatment of Atisara (diarrhoea). The ingredients of Darvyadi Ghrita possess potential anti-diarrheal properties, making it a promising alternative for managing diarrhoeal conditions. Aim & Objectives: The study aims to evaluate the anti-diarrheal activities of Darvyadi Ghrita. The specific objectives include: Preparation of Darvyadi Ghrita as per Sharangdhar Samhita. Analytical evaluation of the formulation based on Ayurvedic and modern parameters. Assessment of its anti-diarrhoea-causing pathogens. Investigation of its anti-diarrheal effects using a castor oil-induced diarrhoea model in experimental animals. Materials & Methods: Preparation: Darvyadi Ghrita was prepared following the classical Ayurvedic method. Anti-diarrheal Study: Evaluated using the castor oil-induced diarrhoea model in mice, analyzing fecal consistency, percentage inhibition, and onset of diarrhoea. Results & Observations: The formulation demonstrated significant anti-bacterial activity, inhibiting the growth of major diarrhoea-causing bacteria. The anti-diarrheal study revealed that a higher dose (12g) exhibited better efficacy compared to medium (10g) and low (8g) doses, reducing diarrhoeal frequency and fecal moisture content. Conclusion: Darvyadi Ghrita possesses notable anti-bacterial and anti-diarrheal properties, supporting its traditional use in Atisara (diarrhoea) management.